PROPORTION AND CHARACTERISTIC OF MYOGENIC LOW BACK PAIN IN UNDERGRADUATE MEDICAL STUDENTS OF UDAYANA UNIVERSITY CLASS OF 2020 - Candra, Alamanda; Widyadharma, I Putu Eka; Tini, Kumara; Wijayanti, Ida Ayu Sri; Wijayanti, Ida Ayu Sri (E-Jurnal Medika Udayana, 2024)
Myogenic low back pain is one type of low back pain that is common but often undiagnosed. Medical students are packed with lecture and study activities so they are more at risk of experiencing low back pain. This study is to determine the proportion, characteristics of sufferers and characteristics of myogenic low back pain in medical students at Udayana University class of 2020. This study is a descriptive cross-sectional study with a sample size of 90 people who meet the inclusion criteria. Sampling using consecutive sampling method. Data collection by filling out an online questionnaire via Google Form and checking the presence of MPS through palpation by a neurology resident. Data analysis was performed using SPSS version 25. The proportion of myogenic low back pain sufferers in medical student class of 2020, Udayana University was 26.7%. The characteristics of the majority of sufferers were 20 years old (41.7%), female (70.8%), normal BMI (91.7%), occasional exercise (62.5%), sitting duration ?4 hours (95.8%), and hunched sitting position (75%). The characteristics of myogenic low back pain were mostly acute (62.5%), pain was felt gradually (62.5%), and the pain scale was mild (54.2%). Respondents mostly chose non-pharmacological therapy by lying down or stretching (95.8%). Out of the 90 respondents who were included in the inclusion criteria in this study, there were 24 (26.7%) respondents who experienced myogenic low back pain with different characteristics from previous studies. Further research with a larger population and causal relationship studies needs to be done to find out the exact cause of myogenic low back pain and how to avoid it.